PRACTICING DIGITAL ETHICS IN SOCIAL MEDIA COMMUNICATION: PERSPECTIVES FROM GENERATION Z STUDENTS - Nur Salsabila Sulaeman; Fatimah Hidayahni Amin; Indrawaty Asfah (Bahasa Inggris Program Sarjana Terapan, Universitas Negeri Makassar, 2026)
This study investigates how Generation Z students at Universitas Negeri Makassar apply digital ethics in their communication through Instagram. Using a descriptive qualitative approach, this study involved eight participants selected via purposive sampling. The findings reveal that students mainly express emotions, gratitude, and appreciation using captions and comments, applying netiquette and privacy principles actively. However, other digital ethics principles like fairness, respect, and responsibility are mostly understood in perception rather than shown in practice. The study contributes to digital communication studies by revealing the gap between awareness and application of ethical communication.